Volunteered Geographic Information (VGI) for the Spatial Planning of Flood Evacuation Shelters in Jakarta, Indonesia - Kusumo, A. N. L. (CRC Press, 2020)
The research discussed in this chapter investigates the advantages and disadvantages of using VGI for capturing residents’ preferences for (official and unofficial) flood evacuation shelters and explores the usefulness of this information for urban planning. We were motivated to carry out this study by the observation that official evacuation shelters provided by the authorities are frequently not used by residents – a fact known, for example, within Jakarta’s city planning department for a long time (one of us works there) and established by research at least 30 years ago (Perry, 1979). A variety of factors determine people’s use of official and non-official evacuation shelters (Stein et al., 2010). According to Rahman et al. (2014), these include aspects such as drainage capacity, soils, technical feasibility, shelter capacities, basic facilities present, environmental impact, acces-sibility, land availability and levels of maintenance. Additional reasons are to be uncovered by our research. We used Twitter data related to flooding in Jakarta, Indonesia to address this objective and the role of VGI.